Salmonella Knowledge, Attitudes and Practices: A Survey of Backyard Poultry Owners Residing in Seattle, Washington and the Surrounding Metropolitan Area. (22nd June 2016) - Kauber, K.; Fowler, H.; Lipton, B.; Meschke, J. S.; Rabinowitz, P.
Summary: Raising poultry flocks in urban backyard settings is becoming increasingly popular across the United States, but carries a risk of zoonotic infection. In the United States from 1990 to 2014, 53 outbreaks of human salmonellosis linked to live poultry have been documented resulting in 2611 known illnesses, 387 known hospitalizations and five known deaths (Centers for Disease Control and Prevention 2015a, http://www.cdc.gov/healthypets/resources/dont-play-chicken-with-your-health-poster-24x36_508.pdf ). A cross‐sectional descriptive study was developed to better understand knowledge, attitudes and practices of urban backyard poultry owners regarding Salmonella risk and prevention. The study included a survey of bird health, animal husbandry and hygiene practices, and knowledge, attitudes and practices relating to Salmonella risk. Participants were videotaped while caring for their birds, and the recordings were transcribed using notational analysis to determine whether reported practices differed from observed practices. The results indicated that while a large proportion of participants knew that exposure to Salmonella is an inherent risk associated with raising poultry and harvesting eggs, their reported and observed practices would not consistently reduce risk of transmission of Salmonella and other zoonotic diseases. Approximately one in four participants reported performing practices that increase risk of inoculation, such as snuggling and kissing birds or eating/drinking near them. None of the participants were observed kissing their birds on video; however, snuggling (holding birds to clothes) or touching their face during routine care was observed in approximately two‐thirds of the video recordings. The video data provided a unique opportunity to compare reported practices with actions recorded during site visits. While the differences were not statistically significant, findings from our study suggest that flock owners may not accurately report the frequency with which risky practices are performed during routine animal care. Education and outreach targeting backyard flock owners should aim to improve husbandry and hygiene practices and reduce risk of zoonotic diseases associated with raising poultry in the backyard setting.